Fungal Spore Diversity and Abundance in Five Areas in Ibadan, South West, Nigeria - Adeyinka Odebode; Adedotun Adekunle (Masters Program in Public Health, 2023)
Background: Airborne fungal spores may pose as a potential high risk of fungalrelated health problems in humans, animals, and plants which necessitated the need to constantly monitor the presence and diversity of fungi spores in the atmosphere regularly. This study aims to investigate diversity and abundance of airborne fungal spores across multiple locations for two years in Ibadan, South West, Nigeria.Subjects dan Method: Study descriptive cross-sectional are used to investigate diversity and abundance of airborne fungal spores across multiple locations. The variable in this study were Airborne fungi spores diversity sampled monthly from five different locations in Ibadan, Oyo State, SouthWest Nigeria for two years using the open plate sedimentation method with the petri dishes of Dichloranglycerol 18 (DG18) and Potato Dextrose Agar (PDA) media. Monthly Meteorological parameters were equally taken during the duration of sampling. The data were collected and graphical presented using histograms.Results: A total of 39 fungal species were identified throughout duration of study. Aspergillus and Penicillium were the most abundant fungi genera isolated while few Zygomycetes, Ascomycetes, and Basidiomycetes were found. Rainy season period favours high number of fungi in the atmosphere. The highest abundance of fungal spores was recorded in June and July while lower fungi concentration was recorded between December and February.Conclusion: the study revealed the most dominant and abundant spores belong to the genera Aspergillus, Penicillium, and Fusarium. The results show the need for people suffering from fungi sensitivity and allergies to be well informed. Keywords: fungi, health, Ibadan, airborne. Correspondence: Adeyinka Odebode. Department of Basic Science, Kampala International University, Uganda. Email: odebode04@yahoo.co.uk.